2014
DOI: 10.1111/jcpe.12249
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antimicrobial photodynamic therapy in the management of chronic periodontitis: a randomized controlled clinical trial

Abstract: Antimicrobial photodynamic therapy acts as a beneficial adjunct to SRP in non-surgical treatment and management of chronic periodontitis in short-term. Further studies are required to assess the long-term effectiveness of aPDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 39 publications
2
97
0
12
Order By: Relevance
“…Eight out of the 18 studies have reported statistically significantly higher improvements in probing depth (PD) reduction and/or clinical attachment (CAL) gain following SRP + PDT compared to SRP alone, [21][22][23][24][25][26][27][28] _ENREF_22while the rest of 10 studies have failed to reveal statistically significant differences in these parameters. 29,[30][31][32][33][34][35][36][37][38] An additional improvement for the reduction of bleeding on probing (BOP) following the use of PDT was reported in 5 out of the 19 papers.…”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 99%
“…Eight out of the 18 studies have reported statistically significantly higher improvements in probing depth (PD) reduction and/or clinical attachment (CAL) gain following SRP + PDT compared to SRP alone, [21][22][23][24][25][26][27][28] _ENREF_22while the rest of 10 studies have failed to reveal statistically significant differences in these parameters. 29,[30][31][32][33][34][35][36][37][38] An additional improvement for the reduction of bleeding on probing (BOP) following the use of PDT was reported in 5 out of the 19 papers.…”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 99%
“…Dessa forma, as três concentrações do azul de toluidina e azul de metileno utilizadas foram 0,05 mg/ml (BERAKDAR et al, 2012;BALATA et al, 2013;PINHEIRO et al, 2010) ,0,1 mg/ml (AL-ZAHRANI et al, 2009;GE et al, 2011;NORO FILHO et al, 2012;THEODORO et al, 2012;BASSIR et al, 2013;FRANCO et al, 2014;MONGARDINI;DI TANNA;PILLONI, 2014) e 10 mg/ml (DE OLIVEIRA et al, 2007;CHRISTOULIDES et al, 2008;CHONDROS et al, 2009;DE OLIVEIRA et al, 2009;LULIC et al, 2009;POLANSKY et al, 2009;SIGUSCH et al, 2010;CAPPUYNS et al, 2012;GIANNOPOULOU et al, 2012;NOVAES et al, 2012;ANDRADE et al, 2013;CAMPOS et al, 2013;LUCHESI et al, 2013;SOUZA et al, 2013;ARWEILER et al, 2014;BETSY et al, 2014;KOLBE et al, 2014;MACEDO et al, 2014;MOREIRA et al, 2014;PETELIN et al, 2014;QUEIROZ et al, 2014;ALWAELI;KHATEEB;AL-SADI, 2015;QUEIROZ et al, 2015). Apesar dos resultados do teste de concentração dos corantes, onde a concentração de 10mg/ml foi a única efetiva para o metileno e a de 5 e 10mg/ml foram as bactericidas para o toluidina, optamos por testar novamente as três concentrações mais comum na literatura acima citada.…”
Section: Discussionunclassified
“…Outros estudos também aplicam essa potência (BRAUN et al, 2008;RÜHLING et al, 2010;GIANNELLI et al, 2012;GIANNOPOULOU et al, 2012;BALATA et al, 2013;DILSIZ;CANAKCI;AYDIN, 2013;ALWAELI;KHATEEB;AL-SADI, 2015). Porém ,outro valor de potência frequentemente encontrado é entre 60 mW e 75 mW (DE OLIVEIRA et al, 2007;CHRISTOULIDES et al, 2008;CHONDROS et al, 2009;DE OLIVEIRA et al, 2009;LULIC et al, 2009;POLANSKY et al, 2009;SIGUSCH et al, 2010;ANDRADE et al, 2013;CAMPOS et al, 2013;LUCHESI et al, 2013;SOUZA et al, 2013;BETSY et al, 2014;CHITSAZI et al, 2014;FRANCO et al, 2014;KOLBE et al, 2014;MACEDO et al, 2014;PETELIN et al, 2014;QUEIROZ et al, 2014;QUEIROZ et al, 2015). Por isso optou-se por testar dois valores de potência: 70 e 100 mW.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ge et al (2011) mostraram redução no sangramento à sondagem no grupo que recebeu aPDT. Os melhores resultados foram obtidos no estudo com a maior população obtendo-se redução em todos os parâmetros clínicos por 6 meses (BETSY et al, 2014). Destaca-se que o tempo de pré-irradiação nessa pesquisa foi de 3 minutos.…”
Section: Pesquisas Em Humanosunclassified